Methods in the physics of porous media - Wong, Po-zen (Experimental methods in the physical sciences, 1999)
Over the past 25 years, the field of VUV physics has undergone significant developments as new powerful spectroscopic tools, VUV lasers, and optical components have become available. This volume is aimed at experimentalists who are in need of choosing the best type of modern instrumentation in this applied field. In particular, it contains a detailed chapter on laboratory sources. This volume provides an up-to-date description of state-of-the-art equipment and techniques, and a broad reference bibliography. It treats phenomena from the standpoint of an experimental physicist, whereby such topics as imaging techniques (NMR, X-ray, ultrasonic, etc.) computer modeling, eletro-kinetic phenomena, diffusion, non-linear wave propagation surface adsorption/desorption, convective mixing, and fracture are specifically addressed.